Effect of glenohumeral elevation on subacromial supraspinatus compression risk during simulated reaching. Issue 10 (27th March 2017) - Lawrence, Rebekah L.; Schlangen, Dustin M.; Schneider, Katelyn A.; Schoenecker, Jonathan; Senger, Andrea L.; Starr, William C.; Staker, Justin L.; Ellermann, Jutta M.; Braman, Jonathan P.; Ludewig, Paula M.
ABSTRACT: Mechanical subacromial rotator cuff compression is one theoretical mechanism in the pathogenesis of rotator cuff disease. However, the relationship between shoulder kinematics and mechanical subacromial rotator cuff compression across the range of humeral elevation motion is not well understood. The purpose of this study was to investigate the effect of humeral elevation on subacromial compression risk of the supraspinatus during a simulated functional reaching task. Three‐dimensional anatomical models were reconstructed from shoulder magnetic resonance images acquired from 20 subjects (10 asymptomatic, 10 symptomatic). Standardized glenohumeral kinematics from a simulated reaching task were imposed on the anatomic models and analyzed at 0, 30, 60, and 90° humerothoracic elevation. Five magnitudes of humeral retroversion were also imposed on the models at each angle of humerothoracic elevation to investigate the impact of retroversion on subacromial proximities. The minimum distance between the coracoacromial arch and supraspinatus tendon and footprint were quantified. When contact occurred, the magnitude of the intersecting volume between the supraspinatus tendon and coracoacromial arch was also quantified. The smallest minimum distance from the coracoacromial arch to the supraspinatus footprint occurred between 30 and 90°, while the smallest minimum distance to the supraspinatus tendon occurred between 0 and 60°. The magnitude of humeral retroversion did not significantly affect minimum distance to the supraspinatus tendon except at 60 or 90° humerothoracic elevation. The results of this study provide support for mechanical rotator cuff compression as a potential mechanism for the development of rotator cuff disease. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2329–2337, 2017.